Anti-Quorum Sensing Potential of Antioxidant Quercetin and Resveratrol - Erdönmez,Demet (2018)
ABSTRACT Quorum sensing system plays an active role in the regulation of pathogenicity of many microorganisms. Inhibition of pathogenicity or virulence factors will increase the success of treatment by preventing the development of antibiotic resistance. In this study, anti-quorum sensing activities of quercetin and resveratrol compounds, which have antioxidant property without damaging to host, have been determined via using biosensor bacteria: Chromobacterium violaceum ATCC 12472 and Chromobacterium violaceum CV026. As quorum sensing inhibitors, quercetin and resveratrol's cutting off the bacterial communication will prevent the treatment failures caused by the development of bacterial resistance. The development of layered drugs with antioxidant compounds such as quercetin and resveratrol will pave the way for new horizons for new therapeutic strategies.